Potential contributions of biotechnologies in the management and conservation of forest resources of the Congo basin - Sonwa, D.J.; Weise, Stephan F.; Nkongmeneck, A.B.; Nwaga, D.; Zapfack, L.; Nzooh, L.Z.; Janssens, M.J.J. (2005)
A review of the potential for biotechnology to contribute to the management and conservation of forest resources in the Congo Basin suggests that biotechnology needs to be seen as a complementary tool to the traditional management programme not as a substitute. In addition, there is a pressing need to support human and material capacity building linked to the application of biotechnology for forestry resource management in the Basin.